Comparison of Serological Response to Doxycycline versus Benzathine Penicillin G in the Treatment of Early Syphilis in HIV-Infected Patients: A Multi-Center Observational Study - Tsai, Jen-Chih (Public Library of Science, 2014)
BACKGROUND: While doxycycline is recommended as an alternative treatment of syphilis in patients with penicillin allergy or intolerance, clinical studies to compare serological response to doxycycline versus benzathine penicillin in treatment of early syphilis among HIV-infected patients remain sparse. METHODS: We retrospectively reviewed the medical records of HIV-infected patients with early syphilis who received doxycycline 100 mg twice daily for 14 days (doxycycline group) and those who received 1 dose of benzathine penicillin (2.4 million units) (penicillin group) between 2007 and 2013. Serological responses defined as a decline of rapid plasma reagin titer by 4-fold or greater at 6 and 12 months of treatment were compared between the two groups. RESULTS: During the study period, 123 and 271 patients in the doxycycline and penicillin group, respectively, completed 6 months or longer follow-up. Ninety-one and 271 patients in the doxycycline and penicillin group, respectively, completed 12 months or longer follow-up. Clinical characteristics were similar between the two groups, except that, compared with penicillin group, doxycycline group had a lower proportion of patients with secondary syphilis (65.4% versus 41.5%, P<0.0001) and a higher proportion of patients with early latent syphilis (25.3% versus 49.6%, P<0.0001). No statistically significant differences were found in the serological response rates to doxycycline versus benzathine penicillin at 6 months (63.4% versus 72.3%, P = 0.075) and 12 months of treatment (65.9% versus 68.3%, P = 0.681). In multivariate analysis, secondary syphilis, but not treatment regimen, was consistently associated with serological response at 6 and 12 months of follow-up. CONCLUSIONS: The serological response rates to a 14-day course of doxycycline and a single dose of benzathine penicillin were similar in HIV-infected patients with early syphilis at 6 and 12 months of follow-up. Patients with secondary syphilis were more likely to achieve serological response than those with other stages.